RESULTS OF LINGUAL FRENECTOMY IN CHILDREN AGED 18 MONTHS TO 3 YEARS AT HAI PHONG CHILDREN'S HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of electrocautery frenectomy in children aged 18–36 months at Hai Phong Children’s Hospital.Materials and Methods: A prospective interventional study without a control group was conducted on 30 children diagnosed with Kotlow class III and IV ankyloglossia classification at Hai Phong Children's Hospital from October 2025 to March 2026. All patients underwent frenectomy using electrocautery under general anesthesia. Anatomical and functional tongue parameters were assessed before and one month after surgery. Postoperative complications including bleeding, pain, swelling, and fever were also recorded. Results: After surgery, 100% of patients achieved normal frenulum attachment and tongue shape. Tongue protrusion improved to 100%, and the ability to reach the upper dental arch increased to 90%. Postoperative bleeding was well controlled, with 100% of patients having no bleeding after 6 hours. Pain and swelling were mostly mild and resolved rapidly, with complete recovery observed by day 7. No major complications were reported; mild postoperative fever occurred in 6.7% of cases.
Keywords: Ankyloglossia, frenectomy, electrocautery, children.